Greenly synthesised biocompatible graphene/zirconia nanocomposite: towards the development of a biosensor for the detection of lung cancer biomarkers - Lin, Lih Poh (2022)
Early detection improves the survival rate of lung cancer. Routine check-up gives rise to early detection, however, conventional screening methods such as X-ray and computed tomography (CT) are incompetent for routine check-up of lung carcinoma due to health hazards associated with repeated exposure to ionizing radiation. These limitations call for a safer, faster, and cheaper solution - the biosensor. In this study, an electrochemical sensor was fabricated using graphene/zirconia (ZG)-modified screen-printed carbon electrode (SPCE). A green approach using solvent exfoliation alongside hydrothermal treatment was employed to prepare the ZG nanocomposites. Material characterisation suggested that pristine graphene and well-hybridised ZG nanocomposite were synthesised. Alongside material characterisation, a cytotoxicity test was performed on the ZG nanocomposite to address the issue of potential hazards during material synthesis and sensor fabrication. The result showed that the ZG nanocomposite had no adverse effects on human lung cells (MRC5) and skin cells (HaCaT), with a half-maximal inhibitory concentration (IC50) value of >500 µg/ml.